Agree as information transmission over dependencies. (9th August 2022) - Ermolaeva, Marina; Kobele, Gregory M.
Abstract: In contemporary Minimalism agreement is the result of a syntactic operation. In contrast to Merge, Agree does not build structure, its role being to transmit morphological features from one head to another. We provide an alternative perspective on agreement in a Minimalist idiom, one that cuts the ontological pie in a different way. Syntax has as its only operation Merge, and agreement, now divorced from syntax, transfers purely morphological information from head to head along channels established via syntactic feature checking. Separating agreement from structure building seems to enable more elegant descriptions of even complicated agreement phenomena.